Consolidating the role of AI in the economy and society: Combating the deepfake phenomenon through strategic and normative approaches. The case of Romania in the EU context - Ionel Bostan (Economies, 2025)
Artificial intelligence (AI) is a field of strategic interest for both the European Union (EU) and its member states, which are making significant efforts to develop and implement AI in a way that is economically and socially beneficial, as well as ethical and secure. This paper analyzes the importance of AI and its impact on the economy and society, highlighting the strategic and regulatory aspects agreed upon at the EU and Romanian levels, given this state's status as an EU member. Based on the latest specialized literature, the first part addresses the concept of AI and emphasizes its role as a key driver of innovation and economic growth. Subsequently, we examine the EU's institutional concerns, outlining the key guidelines and steps in harnessing AI opportunities, as well as the strategic and regulatory milestones that govern AI implementation within the EU. In this context, we focus on the complexities involved in the transition to the AI Era, recent developments, the process of drafting and adopting the EU AI Act, and the significance of the AI Pact. Our study fully reflects that Romania is also taking significant strategic and regulatory measures to align with the demands of the AI Era, with particular attention given to improving the legislative framework regarding the ethical implications of AI implementation and preventing deepfakes.
Keywords: 330; artificial intelligence (AI); implications for economy/society; institutional policies; strategic framework; European/national norms; deepfake; responsible/ethical AI